Microbispora sitophila sp. nov., a novel actinobacterium isolated from rhizosphere soil of wheat (Triticum aestivum L.). Issue 3 (2nd March 2021) - Guo, Lifeng; Li, Zhiqi; Xu, Xi; Pang, Qiuying; Zhao, Junwei
Abstract : A novel actinobacterium, designated strain NEAU-D428 T, was isolated from rhizosphere soil of wheat and characterized using a polyphasic approach. Morphological and chemotaxonomic characteristics of the strain coincided with members of the genus Microbispora . The 16S rRNA gene sequence analysis showed that the isolate was most closely related to Microbispora bryophytorum NEAU-TX2-2 T (99.2 %). Phylogenetic analysis based on the 16S rRNA gene sequences indicated that the strain clustered with Microbispora clausenae CLES2 T (99.1 %), but formed a separate subclade in the phylogenomic tree within the genus Microbispora . The menaquinones were identified as MK-9(H4 ), MK-9(H2 ) and MK-9(H0 ). The phospholipid profile was found to consist of diphosphatidylglycerol, phosphatidylmonomethylethanolamine, phosphatidylethanolamine, ninhydrin-positive glycophospholipid, phosphatidylinositol and phosphatidylinositol mannoside. The major fatty acids were identified as iso-C16 : 0, C16 : 0, 10-methyl C17 : 0 and C18 : 0 . Digital DNA–DNA hybridization and average nucleotide identity values between strain NEAU-D428 T and M. bryophytorum NEAU-TX2-2 T, Microbispora camponoti 2C-HV3 T, M. clausenae CLES2 T, ' Microbispora cellulosiformans' Gxj-6 T and Microbispora fusca NEAU-HEGS1-5 T were 47.6 and 92.2 %, 47.5 and 92.2 %, 55.9 and 94.0 %, 33.1 and 86.8 %, and 33.6 and 87.1 %, respectively. These results and some physiological and biochemical properties demonstrated that the strain could be distinguished from its closest relatives. Therefore, it is proposed that strain NEAU-D428 T should be classified as representative of a novel species of the genus Microbispora, for which the name Microbispora sitophila sp. nov. is proposed. The type strain is NEAU-D428 T (=CGMCC 4.7523 T =DSM 109822 T ).